VISUAL PERCEPTION AND STORYTELLING IN MALAYALAM CINEMA: A CASE STUDY OF NANPAKAL NERATHU MAYAKKAM - C S, Salin Dhas; Kumar, S. Rajesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Visual storytelling, an effective narrative technique utilized to elicit emotions and convey information to the audience through various facets. Cinematography is a key medium for visual storytelling. The acclaimed Indian film director Mani Rathinam enables the portrayal of emotions and meanings through each shot. This study delves into the Malayalam film "Nanpakal Nerathu Mayakkam," directed by Lijo Jose Pellisserry and cinematography by Theni Eswar. The film has garnered critical acclaim for its immersive narrative techniques, camera shots, and angles. The research focuses on gauging the audience's perception and involves an in-depth analysis of framing, composition, color utilization, and lighting techniques employed in the film during the production stage to narrate the story naturally to the audience.